Racial/ethnic differences in the associations between trust in the U.S. healthcare system and willingness to test for and vaccinate against COVID-19 - Judy Nanaw; Juliana S. Sherchan; Jessica R. Fernandez; Paula D. Strassle; Wizdom Powell; Allana T. Forde (BMC, 2024)
Abstract Background Trust in the healthcare system may impact adherence to recommended healthcare practices, including willingness to test for and vaccinate against COVID-19. This study examined racial/ethnic differences in the associations between trust in the U.S. healthcare system and willingness to test for and vaccinate against COVID-19 during the first year of the pandemic. Methods This cross-sectional study used data from the REACH-US study, a nationally representative online survey conducted among a diverse sample of U.S. adults from January 26, 2021-March 3, 2021 (N = 5,121). Multivariable logistic regression estimated the associations between trust in the U.S. healthcare system (measured as "Always", "Most of the time", "Sometimes/Almost Never", and "Never") and willingness to test for COVID-19, and willingness to receive the COVID-19 vaccine. Racial/ethnic differences in these associations were examined using interaction terms and multigroup analyses. Results Always trusting the U.S. healthcare system was highest among Hispanic/Latino Spanish Language Preference (24.9%) and Asian (16.7%) adults and lowest among Multiracial (8.7%) and Black/African American (10.7%) adults. Always trusting the U.S. healthcare system, compared to never, was associated with greater willingness to test for COVID-19 (AOR: 3.20, 95% CI: 2.38-4.30) and greater willingness to receive the COVID-19 vaccine (AOR: 2.68, 95% CI: 1.97-3.65). Conclusions Trust in the U.S. healthcare system was associated with greater willingness to test for COVID-19 and receive the COVID-19 vaccine, however, trust in the U.S. healthcare system was lower among most marginalized racial/ethnic groups. Efforts to establish a more equitable healthcare system that increases trust may encourage COVID-19 preventive behaviors.